2020
DOI: 10.2141/jpsa.0180143
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adding Phytase from <i>Aspergillus niger</i> to a Low Phosphorus Diet on Growth Performance, Tibia Characteristics, Phosphorus Excretion, and Meat Quality of Broilers 35 days after hatching

Abstract: This study was designed to determine the effect of phytase extracted from Aspergillus niger (Natuphos ® E) on growth performance, bone mineralization, phosphorous excretion, and meat quality parameters in broilers fed available phosphorous (aP)-deficient diet. In total, 810 one-day-old Indian River broilers were randomly allotted into one of three dietary treatments, with six replicates per treatment. The three dietary treatments were 1) control group (CON: basal diet with sufficient aP), 2) low phytase (LPY: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
(43 reference statements)
1
4
1
Order By: Relevance
“…Contrary to previous work [63] and what may be expecteda reduction in P content of the diet (NC) resulted in greater P excretion than birds offered diets with a higher P content, despite reduced feed intake. This increase in P excretion may be a result of the slight reduction in P digestibility of NC birds.…”
Section: Phytase and N And P Excretioncontrasting
confidence: 90%
“…Contrary to previous work [63] and what may be expecteda reduction in P content of the diet (NC) resulted in greater P excretion than birds offered diets with a higher P content, despite reduced feed intake. This increase in P excretion may be a result of the slight reduction in P digestibility of NC birds.…”
Section: Phytase and N And P Excretioncontrasting
confidence: 90%
“…We confirmed that the CP and P excretions of broilers fed the NC1500 diet 22% and 32.6% lower, respectively than those fed the PC diet ( Table 4 ). These results are supported by Srikanthithansan et al [ 29 ] who observed that less P was excreted by broilers fed a low phosphorus diet (3.0% avP/kg) supplemented with 500 to 1000 FTU/kg phytase than those fed a normal P diet (4.5% avP/kg). Walk and Olukosi [ 30 ] also reported that broilers fed a phytase-supplemented diet (2,000 or 4,000 FTU/kg) showed a higher CP digestibility, together with less CP excreted.…”
Section: Discussionsupporting
confidence: 73%
“…Ultimate pH, color, drip loss, cook loss, water holding capacity (WHC), oxidative stability (thiobarbituric acid reactive substances [TBARS]), and tenderness (shear force value) were measured as previously described [ 20 ].…”
Section: Methodsmentioning
confidence: 99%